Prevalence and Molecular Characteristics of FAdV-4 from Indigenous Chicken Breeds in Yunnan Province, Southwestern China - Jinyu Lai; Liangyu Yang; Fashun Chen; Xingchen He; Rongjie Zhang; Yong Zhao; Gan Gao; Weiwu Mu; Xi Chen; Shiyu Luo; Tao Ren; Bin Xiang (Microorganisms, 2023)
Fowl adenovirus-induced hepatitis–pericardial effusion syndrome outbreaks have been increasingly reported in China since 2015, resulting in substantial economic losses to the poultry industry. The genetic diversity of indigenous chicken results in different immune traits, affecting the evolution of these viruses. Although the molecular epidemiology of fowl adenovirus serotype 4 (FAdV-4) has been well studied in commercial broiler and layer chickens, the prevalence and genetic characteristics of FAdV-4 in indigenous chickens remain largely unknown. In this study, samples were collected from six indigenous chicken breeds in Yunnan province, China. FAdV-positive samples were identified in five of the six indigenous chicken populations via PCR and 10 isolates were obtained. All FAdVs belonged to serotype FAdV-4 and species FAdV-C. The hexon, fiber, and penton gene sequence comparison analysis demonstrated that the prevalence of FAdV-4 isolates in these chickens might have originated from other provinces that exported chicks and poultry products to Yunnan province. Moreover, several distinct amino acid mutations were firstly identified in the major structural proteins. Our findings highlighted the need to decrease inter-regional movements of live poultry to protect indigenous chicken genetic resources and that the immune traits of these indigenous chickens might result in new mutations of FAdV-4 strains.